Donor Site Wound Healing in Radial Forearm Flap: A Comparative Study Between Dermal Substitute and Split-Thickness Skin Graft Versus Full-Thickness Skin Graft Primary Coverage. Issue 6 (June 2021) - Di Giuli, Riccardo; Dicorato, Paolo; Kaciulyte, Juste; Marinari, Niccolò; Conversi, Francesco; Mazzocchi, Marco
Abstract : Abstract: Radial forearm flap (RFF) is one of the most used flaps in reconstructive surgery. Despite its versatility and effectiveness, the donor site is affected by aesthetic and functional issues. In the group of techniques described to improve the donor site morbidity, dermal substitutes offer a valid approach in the wound management. A bilayered bioresorbable dermal substitute (Hyalomatrix) was used to provide the primary coverage of the RFF harvest site followed after 3 weeks by a split-thickness skin graft placement. In this study, 37 patients underwent RFF donor site reconstruction and subjected to a minimum follow-up of 1 year. The dermal substitute was applied on 15 patients, and their outcomes were compared with the data achieved by 22 patients submitted to immediate reconstruction with autologous full-thickness skin graft. Results were documented by digital photographs, the visual analog scale, the Vancouver Scar Scale, and the Disabilities of the Arm, Shoulder, and Hand questionnaire. Data were analyzed and compared through statistical analysis. Total wound coverage was achieved in 4 to 6 weeks, and no tendon impairments were reported in the dermal substitute group. In our experience, the use of the dermal substitute is a valuable mean to minimize RFF donor site morbidity with excellent functional and aesthetic outcomes.